Російське кавказознавство: історія, проблеми та напрями - Анчабадзе, Ю.; Булатов, А. (Народна творчість та етнографія, 2010)
Статья освещает длительный процесс становления и развития российского кавказоведения как особенной отрасли исторического и этнологического знания. Аккумулированный этой дисциплиной фактологический и теоретический материал, по мнению авторов, в значительной степени определит специфику социокультурного бытия Кавказа в XXI в. The article elucidates the long process of the appearance and the development of the Russian Caucasus studies as a specific historical and ethnological branch. In the author’s view, the factological and theoretical material accumulated by the scientific branch would determine to a great extent the Caucasian sociocultural specifics in the XXIst century.